Internet of Things (IoT) in Agriculture: The Idea of Making the Fields Talk - Vadlamudi, Siddhartha (Engineering International, 2020)
The demand for agricultural crops is moving at a slower pace compared to the human population. There must be increased agricultural productivity. Ongoing innovative advances have added to the ascent of exactness agribusiness, empowering farmers to settle on better choices with more data about their soil, water, yield, and local environment, yet has been generally restricted to popularized and production of cash crops. The objective of smart agribusiness research is to ground a dynamic emotionally supportive network for the management of farms. IoT is being used in agriculture to get to know the crop field by utilizing sensors for monitoring, controlling in the field. It is used to get to know the crop field by utilizing sensors for monitoring, controlling in the field, etc. Recent developments in IoT, comparison between traditional and smart agriculture, and the roles of IoT in agriculture were analyzed in this study. The articles were purposively inspected while the qualitative data gathered was dissected utilizing content analysis. Summarily, the rise of smart agriculture has lowered the practice of traditional farming, as it has enhanced it in no small way. The research likewise showed that the lacuna in agriculture can be filled with IoT. Scalability in technology should be encouraged without affecting the functionalities of the existing infrastructures.
Keywords: Agriculture; Innovation; Internet of Things; Sensor; Scalability